Estudo epidemiológico da dengue em Cascavel e outros Municípios da Décima Regional de Saúde do Estado do Paraná - Silva, Suelem Leite da (2018)
Introduction: So-called Neglected Tropical Diseases (NTDs) have been a problem for society for many years. Among the most prevalent NTDs are dengue, a viral disease caused by different serotypes of the dengue virus (DENV), transmitted from the female bite of the Aedes Aegypti (Diptera: Culicidae) mosquito. Dengue can be avoided and treated, but most of the time the vector is not controlled, preventing the fight against the transmission of the disease. Dengue prevention has become a major challenge because its transmission is influenced by several factors, such as environmental, climatic, social and economic factors. The presentation of the disease comprises from mild clinical forms, to severe bleeding and shock, and can progress to death. Objectives: To analyze the cases of classical dengue, dengue fever with signs of alarm (DSA), severe dengue (DG) and deaths in the municipalities of the Tenth Regional Health and correlate with the number of cases in other municipalities of Paraná. To evaluate the regions of the municipality of Cascavel-PR with greater risk of contracting the disease and the influence of temperature, precipitation and environmental conditions on dengue transmission. Methodology: This dissertation consists of a descriptive, cross - sectional and retrospective study of the reports of dengue cases in their different clinical forms and confirmed deaths in the municipalities of the 10th Regional of Health of the State of Paraná in relation to the epidemiological situation of dengue in other municipalities of the state. Information on the municipalities of the 10th Regional Health Service was collected from the National System of Notifiable Diseases System of the 10th Regional from August 2012 to July 2017. Data for other municipalities in Paraná were obtained from of public data made available through the epidemiological bulletins on the website of the State Health Department. The comparison of the dengue cases in the municipalities of the 10th Regional and Paraná were performed by means of the Qui Quadrado analysis for k proportions, assuming a level of significance of 0.05. Data on the municipality of Cascavel-PR were obtained by the Municipal Health Department from 2012 to 2016. Based on the number of dengue cases in this municipality, an endemic channel was constructed, which makes it possible to determine outbreak and epidemic situations, defined by means of the calculation of the median, 1st and 3rd quartiles of the number of confirmed cases in Cascavel monthly from January 2012 to December 2016. Also, the georeferencing was done from the residential addresses of the confirmed cases of the disease through QGIS Geographic Information System (2016). With the identification of the areas with the highest concentration of dengue cases, on-site visits to strategic regions were carried out to verify the environmental conditions and presence of indicators that could be influencing the occurrence of the number of cases and transmission of the disease. In addition, data were collected from the Environmental Surveillance for LIRAa (Rapid Survey of Infestation Index for Aedes aegypti), which is a larval sampling of Aedes aegypti done every three months in Cascavel to obtain the infestation estimate by the vector. The temperature and precipitation data were requested from the Paraná Meteorological System (SIMEPAR). The dengue case numbers and the environmental variables were evaluated monthly on the distribution pattern of the data through the Shapiro-Wilk test. Results: In the municipalities of the 10th Region 26 cases of Dengue with alarm signs (DSA), 4 cases of severe Dengue (DG) and 1 death were reported. In Paraná there were 1,487 cases of DSA, 381 cases of DG and 117 deaths. As for DSA cases, in the total number of cases accumulated between the epidemiological periods from 2012 to 2017, there was a lower frequency of cases reported by the Tenth Regional when compared to the number reported throughout the state (p = 0.007). When evaluating the number of cases of DG, in total the frequency reported in the Regional Tenth is significantly lower (0.08%) than in the rest of Paraná (0.23%, p = 0.031). The frequencies of the number of deaths observed between the Tenth Regional and the Paraná State reports were statistically similar in all epidemiological periods (p> 0.05). In the municipality of Cascavel, through the analysis of the endemic channel, it was verified that in 2012, all months were in the control zones, with the exception of October; in 2013, they were in these areas every month; in 2014, 3 months were not found in these security zones (October, November and December); in 2015, 4 months were outside these security zones (May, June, August and December); in 2016, only the month of December showed up in the security zone. With the georeferencing, the heat maps showed that there is a predominance of positive dengue cases in the western, central and southern regions of the municipality, which includes the Santa Cruz, Alto Alegre, Coqueiral, Neva, Parque São Paulo and Centro neighborhoods. majority of the evaluated periods. During the on-site inspection to verify the environmental conditions in the neighborhoods where there was a recurrent concentration of cases, as verified in the heat maps, numerous sites were found that can serve as breeding sites for Aedes aegypit, among which: old iron, garbage and debris such as water boxes, bottles, furniture and appliances thrown in the open and surrounding. The first cycle of the LIRAa of 2016 showed one of the highest rates of infestation during the period evaluated, during this period the whole municipality was in a situation of alert or risk of contracting the disease. The correlations of dengue cases and temperature (minimum, mean and maximum) and precipitation showed a weak association only between the prevalence of Cascavel the dengue cases and the maximum temperature. The minimum, mean and precipitation temperatures did not present significant correlations with the incidence of dengue cases. Conclusion: The Tenth Regional has presented increasing percentages of dengue cases in relation to Paraná, and in the last epidemiological period it represented 10% of all cases in the state. Efforts and actions are needed to focus on reducing dengue cases, especially in municipalities with high incidence. Although this work demonstrates geographically the residences of individuals who contracted dengue and the places with the highest risk and meeting of breeding sites in the regions of Cascavel, it is not possible to affirm the causes of dengue cases in the period evaluated. The environmental variables such as temperature and precipitation did not present a strong correlation with the cases of dengue in Cascavel. Further studies and analyzes are necessary to relate these variables to the situations presented, which are intervening in the spread of dengue in the municipality. It is recommended that studies with more specific designs be designed to analyze individual and environmental factors capable of cooperating to increase the number of dengue cases in these localities.